Avaliação dos aspectos relacionados à conservação do Peixe-boi-amazônico Trichechus inunguis (Natterer, 1883) e da Ariranha Pteronura brasiliensis (Zimmerman, 1780) no Parque Nacional do Viruá, RR-Brasil - Rojas Rojas, Diana Marcela (2009)
This study relates aspects on the amazonian manatees and giant otters's conservation, at the low river Branco, National Park of Viruá, Roraima. The general objective was to verify the status of conservation and knowledge exist threaten to themselves species. The study was designed in two parts: Interviews with ancient residents and fishers of the area, and the verification of these data was accomplished at a stretch of 53 km by the river Iruá. Chisquared tests were used for the analysis of interviews to know if answers were homogenous. The results evidence that people have a good knowledge on the places of use, and some behaviors of species. “Ressacas”, “Lagos” e “Remansos” were the more places mentioned for the amazonian manatee, as well as banks and flooded forests for giant otters. Vestiges of consumption in subaquatic's Cyperaceous are the hard signals of amazonian manatee presence at the river Iruá. Dens, latrines and campsites distributed in banks and flooded forests show that giant otters utilize the river's canal well, having an occupation of the 23% of they. Aspects related to the Unit of Conservation and of his surroundings are discussed. For the moment, the amazonian manatees and giant otters are not threatened in the area of the study, but, inspectorate and supervision must be intensified, implementation of studies in situ with these species, divulgation of programs of environmental education, and sensitization to local level like a Roraima's state.